2013
DOI: 10.1590/1516-4446-2012-0977
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline, clomipramine, and maprotiline attenuate the inflammatory response by inhibiting neutrophil migration and mast cell degranulation

Abstract: Objective: Despite the recognized anti-inflammatory potential of heterocyclic antidepressants, the mechanisms concerning their modulating effects are not completely known. Thus, we evaluated the anti-inflammatory effect of amitriptyline, clomipramine, and maprotiline and the possible modulating properties of these drugs on neutrophil migration and mast cell degranulation. Methods: The hind paw edema and air-pouch models of inflammation were used. Male Wistar rats were treated with saline, amitriptyline, clomip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Hydrated tissue sections (4 μ m) were immersed in 0.1% toluidine blue solution (in 0.9% sodium chloride) per 60s for histochemical assessment (Gurgel et al , ) and mast cell counting using the same methodology (Shaker et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrated tissue sections (4 μ m) were immersed in 0.1% toluidine blue solution (in 0.9% sodium chloride) per 60s for histochemical assessment (Gurgel et al , ) and mast cell counting using the same methodology (Shaker et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Amitriptyline is a tricyclic antidepressant (TCA) that exerts its effect by inhibiting reuptake of the neurotransmitters serotonin, norepinephrine, and to a lesser effect, dopamine (Moore et al, 2012). It has also been shown to inhibit H1 release from mast cells in vitro (Gurgel et al, 2013). While its use in veterinary medicine has been limited primarily to behavioral disorders (Chew et al, 1998;Virga et al, 2001;Overall and Dunham, 2002), research in humans has demonstrated an analgesic effect in those suffering from interstitial cystitis (a urinary bladder disease with a chronic, neurogenic pain component; Hanno et al, 1989), and the drug is commonly used to treat neuropathic pain (Moore et al, 2012).…”
Section: Amitriptylinementioning
confidence: 99%
“…amitriptyline, clomipramine and maprotiline have an important anti-inflammatory role, which is dependent on the modulation of neutrophil migration and mast cell stabilization [109]. A shift in the balance of the inflammation toward an anti-inflammatory state in the hypothalamus i.e.…”
Section: Treat Inflammation In Depressionmentioning
confidence: 99%
“…Unexpectedly, sertraline and docosahexaenoic acid had pro-inflammatory effects, with sertraline increasing interferon alpha and interleukin-6 and docosahexaenoic acid increasing interleukin-15, interleukin-1RA, interferon alpha, and interleukin-6, though these changes were also associated with a decrease in nuclear factor kB activity, suggesting distinct modes of action. Agomelatine and moclobemide had no effect on interleukin-6 secretion [109]. …”
Section: Treat Inflammation In Depressionmentioning
confidence: 99%